Pregunta
upstudy study bank question image url

The graph of \( g(x)=a\left(\frac{1}{5}\right)^{x}-5 \) passes throughi \( (-2 ;-4) \). 7.1 Show that \( a=\frac{1}{25} \) 7.2 Determine the coordinates of the \( x \) intere \( E^{4} f_{8} \), 7.3 Given: \( h(\tau)=\left(\frac{1}{5}\right)^{x} \) 7.3.1 Determine the cquation of \( x^{-1}(x) \), the inverse of \( h \), in the forks \( y=- \) 7.3.2 Describe the transformation from. g to h .

Ask by Stuart Powers. in South Africa
Feb 18,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

a = 1/25 x-intercept of g is at (–3, 0) Inverse of h is h⁻¹(x) = –log₅ x Transformation from g to h: compress vertically by 1/25 and shift down by 5 units

Solución

We are given that   g(x) = a·(1/5)^x – 5 and that the point (–2, –4) lies on the graph of g. We also have a related function   h(x) = (1/5)^x. Below are the steps to solve each part. ───────────────────────────── Step 7.1. Show that a = 1/25 Since (–2, –4) is on the graph of g, we substitute x = –2 and g(–2) = –4 into the equation:   –4 = a·(1/5)^(–2) – 5. Recall that (1/5)^(–2) = 5² = 25. Thus, we have   –4 = a·25 – 5. Now, add 5 to both sides:   –4 + 5 = 25a   1 = 25a. Finally, divide both sides by 25:   a = 1/25. ───────────────────────────── Step 7.2. Determine the coordinates of the x-intercept of g The x-intercept is found by setting g(x) = 0. That is, solve   0 = a·(1/5)^x – 5. We now substitute a = 1/25 into the equation:   0 = (1/25)·(1/5)^x – 5. Add 5 to both sides:   (1/25)·(1/5)^x = 5. Multiply both sides by 25 to isolate (1/5)^x:   (1/5)^x = 125. Recall that 125 = 5³. Also note that (1/5)^x = 5^(–x). Therefore,   5^(–x) = 5³. Since the bases are the same, equate the exponents:   –x = 3 ⟹ x = –3. Thus, the x-intercept is at (–3, 0). ───────────────────────────── Step 7.3. Inverse of h and the transformation from g to h 7.3.1. Find the inverse function h⁻¹ The function is given by   h(x) = (1/5)^x. It is often useful to write this as   h(x) = 5^(–x). To find the inverse, start with   y = 5^(–x). Swap x and y:   x = 5^(–y). Now solve for y by taking the logarithm with base 5 on both sides:   log₅(x) = –y ⟹ y = –log₅(x). Thus, the inverse function is   h⁻¹(x) = –log₅(x). 7.3.2. Describe the transformation from g to h Recall that   g(x) = a·(1/5)^x – 5  with a = 1/25  so that g(x) = (1/25)·(1/5)^x – 5,   h(x) = (1/5)^x. We can express g in terms of h as follows:   g(x) = (1/25)·h(x) – 5. Thus, compared to h, the graph of g is obtained by: 1. Vertically compressing h by a factor of 1/25. 2. Then shifting the resulting graph downward by 5 units. Equivalently, starting with g, if one “undoes” these transformations (that is, first shifting upward by 5 units and then stretching vertically by a factor of 25), one obtains h. ───────────────────────────── Summary of Answers 7.1 a = 1/25. 7.2 The x-intercept of g is at (–3, 0). 7.3.1 The inverse of h is h⁻¹(x) = –log₅ x. 7.3.2 The graph of g is obtained from the graph of h by a vertical compression by a factor of 1/25 followed by a downward shift of 5 units. (Conversely, h can be obtained from g by first shifting upward 5 units and then stretching vertically by a factor of 25.) Any answer equivalent to the above is correct.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To find \( a \) in the equation \( g(x) = a\left(\frac{1}{5}\right)^{x} - 5 \) that passes through the point \( (-2, -4) \), substitute \( x = -2 \) and set \( g(-2) = -4 \). This gives: \[ -4 = a\left(\frac{1}{5}\right)^{-2} - 5 \] Solving for \( a \): \[ -4 + 5 = a \cdot 25 \implies 1 = 25a \implies a = \frac{1}{25} \] Now, let’s find the \( x \)-intercept by setting \( g(x) = 0 \): \[ 0 = \frac{1}{25}\left(\frac{1}{5}\right)^{x} - 5 \] Solving gives: \[ \frac{1}{25}\left(\frac{1}{5}\right)^{x} = 5 \implies \left(\frac{1}{5}\right)^{x} = 125 \implies x = -3 \] So, the \( x \)-intercept is \( E( -3; 0) \). For the inverse of \( h(x) = \left(\frac{1}{5}\right)^{x} \), set \( y = \left(\frac{1}{5}\right)^{x} \), then take the logarithm: \[ x = -\log_{5}(y) \implies y = -\log_{5}(x) \] To describe the transformation from \( g \) to \( h \), you can say that \( h(x) \) is derived from \( g(x) \) by first applying an exponential decay function followed by a vertical stretch by \( a \) and a downward shift by \( -5 \). This gives \( g \) a more transformed appearance, moving it down the graph while scaling its outputs based on the factor \( a \).

preguntas relacionadas

Latest Pre Calculus Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad